Synthesis and characterization of a new Organic â€“ Inorganic sulfate (C5H6N2O)2[Co(H2O)6]3(SO4)4.2H2O - Mathlouthi, M.; Benmansour, S.; Rzaigui, M.; Sta, W. Smirani (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
crystals of a new hybrid compound, (C5H6N2O)2[Co(H2O)6]3(SO4)4.2H2O, were synthesized in aqueous solution and characterized. This compound crystallizes in the triclinic system with the space group P-1, the unit cell :a=6.632(3) Ã…, b=11.769(5) Ã…, c=14.210(6) Ã…, Î±=67.86(4)Â°, Î²=81.32(4)Â°, Î³=85.18(4)Â° and V=1015.14(8) Ã…3 . Its crystal structure can be described as a packing of alternated inorganic and organic layers. The different components are connected by a three-dimensional network of O-Hâ€¦O and N-Hâ€¦O hydrogen bonds.Â